Labile and total particulate element digests from 16° and 17° S shelf transects during METEOR cruise M135 - Ali A Al-Hashem; Eric Pieter Achterberg (PANGAEA, 2025)
Labile and total particulate trace metal concentrations were determined on particles collected from the water column of shelf sections at 16° and 17° S shelf transects on METEOR cruise M135. Samples were collected from the trace metal clean sampling system. Polyethersulfone membrane filters (Sartorius, 0.2 μm) and plastic holders (Swinnex, Nalgene) were pre-cleaned in 1 M HCl followed by de-ionized water, then mounted directly onto the OTE samplers in the trace metal clean laboratory on deck. About 4 L (exact volume recorded) of seawater was passed over the filters. Filters were then rinsed with a few drops of de-ionized water (<2 mL) and stored frozen at -20°C until analysis. Labile and total particulate digestions were conducted in series on the same filters. Filters were leached and digested in perfluoroalkoxy vials (Savillex). Labile particulate metals were determined following a 2-hour weak acid leach (25% by volume acetic acid, Optima grade, Fisher Scientific) with a mild reducing agent (0.02?M hydroxylamine hydrochloride, Sigma TM grade) and a short heating step (10?minutes at 90–95?°C). Total particulate metals were determined following a 15-hour reflux digest at 150°C using a mixture of hydrofluoric acid and nitric acid (50% and 10% by volume, respectively, Optima grade, Fisher Scientific). Metal concentrations were then determined via high resolution inductively coupled plasma-mass spectrometry with calibration via standard additions prepared in a sample-matched matrix.